The Economic Role of Customer Relationship Management in Enhancing Shopping Convenience: An Islamic Business Ethics Approach - Leswara, Malda Davitha; Nurbaiti, Nurbaiti; Yanti, Nursantri (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the implementation of Customer Relationship Management (CRM) in enhancing consumer shopping comfort from the perspective of Islamic business ethics at Farida Fashion Store. A qualitative descriptive approach was employed, using observation, interviews and documentation as data collection methods. The findings reveal that CRM is implemented through personal interactions between employees and customers, without the support of integrated digital systems. Despite this, After implementing CRM, employees became more structured in their customer service, allowing them to maintain their best service for customers such an approach has successfully built customer loyalty and increased satisfaction. From the Islamic business ethics perspective, the store applies five key principles: tauhid (oneness), justice, free will, responsibility, and ihsan (excellence). However, challenges remain, including limited human resources, minimal use of technology. However, challenges remain, such as understaffing and suboptimal technology utilization. With gradual improvements, CRM in this store can be better and provide benefits to both the business and customers.